Institutional changes in the economies of Central and Eastern European countries and the situation of the labour market - Adamczyk, Andrzej (Ekonomika, 2009)
The object of the article is to assess the influence of economic and political institutions on the situation of the labour market in Central and Eastern European countries. In the initial phase of transformation, the debate in these countries focused on economic stabilization. In recent years, the focus shifted towards institutional solutions of economic processes, including the situation of the labour market.The emphasis is put on the particularities of the countries undergoing transformation, in which profound changes in economic and political institutions are taking place due to the implementation of economic reforms, on the one hand, and the democratization process, on the other hand. Undoubtedly, the process of institutional change was occurring at varying pace in Central and Eastern European Countries as a result of various problems of respective labour markets.The analysis, based upon the data from 1995 to 2006, shows that the institutional structure has a great impact on the labour market. The existence of efficient and well-managed institutions help to reduce distortions in the allocation of the labour force as well as creating demand for labour.
Keywords: labour market; labour market institutions; transformation; unemployment